2023
DOI: 10.3390/su15107800
|View full text |Cite
|
Sign up to set email alerts
|

Almonds By-Product Microcrystalline Cellulose as Stucco for Wooden Artifacts

Abstract: Over the years in the field of conservation of cultural heritage, a wide use of traditional products for the plastic reintegration of wooden artifacts has been seen. However, they are usually not designed for this purpose. The present study also shows, in terms of material compatibility, the material most suited for wood restoration, cellulose pulp, from the perspective of a new green approach of reusing waste. Indeed, microcellulose was obtained by simple alkaline treatment from softwood almond shells. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The same MCCs were employed on the basis of their micrometric dimensions, high mechanical strength, and being biodegradable powder in the preparation of stucco for wooden artifacts [65]. Three different stucco formulations were prepared by adding different binders (Aquazol 500, Klucel-c, and a mixture of both) to a cellulose pulp.…”
Section: Almond Shellmentioning
confidence: 99%
See 2 more Smart Citations
“…The same MCCs were employed on the basis of their micrometric dimensions, high mechanical strength, and being biodegradable powder in the preparation of stucco for wooden artifacts [65]. Three different stucco formulations were prepared by adding different binders (Aquazol 500, Klucel-c, and a mixture of both) to a cellulose pulp.…”
Section: Almond Shellmentioning
confidence: 99%
“…The results reveal how the mechanical properties of the stucco were improved by incorporating MCC and how its characteristics changed depending on the binder used (Aquazol 500 proves to be the best for the wood matrix). However, the effects of long-term durability under real conditions, as well as the effectiveness on other materials besides wood, were not investigated [65].…”
Section: Almond Shellmentioning
confidence: 99%
See 1 more Smart Citation
“…An atypical treatment for wood conservation deserves special mention: it has been shown that EOs (Thymus capitatus) can be incorporated into microcrystalline cellulose formulations based on almond-shell cellulose pulp to prepare stuccos with biocidal properties against fungal colonization and insect infestation [211].…”
Section: Novel Application Mechanisms (Encapsulation Gels and Emulsions)mentioning
confidence: 99%